Influence of vermicompost and npk on the growth and protein content of boro rice (Oryza sativa L.) (Journal of Biodiversity Conservation and Bioresource Management, 2020)
Influence of vermicompost (2.5, 5, 7.5 and 10 ton/ha), Nitrogen (12, 24, 36, 48 and 60 kg/ha), phosphorus (4, 8, 12, 16 and 20 kg/ha) and potassium (10, 20, 30, 40 and 50 kg/ha) on the growth and protein contents of Boro rice (Oriza sativa L.) was examined. Highest height (93.03cm), leaf number (23 no/plant), highest productive plants observed (8.67 no/pot), vegetative plants (8.0 no/pot), dry weight of panicle per plant (9.45 g), length of panicle (22.37 cm), number of grains per panicle (153.33),1000-grain weight (21.56 g) and the maximum dry weight (28.15 g/plant) were observed in VC10 ton/ha + N12P4K10 kg/ha treatments. Highest concentrations of protein content (29.875%), P (0.478%), K (5.20%) and S (0.182%) were in N60P20K50 kg/ha. Results showed that the overall best growth performance and yield were achieved in VC10 ton/ha + N12P4K10 kg/ha treatments.J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(2): 69-74